Synergistic therapeutic effect of arsenic trioxide and radiotherapy in BALB/C nude mice bearing nasopharyngeal carcinoma xenografts - Xie, L.X.; Lin, X.H.; Li, D.R.; Chen, J.Y.; Hong, C.Q.; Du, C.W. (Experimental Oncology, 2007)
It has been shown that arsenic trioxide (ATO) induced apoptosis in human nasopharyngeal carcinoma cells and inhibited the growth of nasopharyngeal carcinoma xenografts (NPCX) in nude mice. Aim: The present study was designed to determine whether ATO at the non-toxic dose level could potentiate the therapeutic effectiveness of radiation therapy in nasopharyngeal carcinoma, using a BALB/C nude mouse xenograft model. Methods: The mice bearing NPCX were treated with radiation alone (2, 4, and 6 Gy), ATO alone (4 mg/kg/day x 6 days), and ATO plus radiation at the same dosage levels. Time of tumor growth delay (defined as the time necessary for the tumor to grow four-fold of its initial volume after, compared with untreated tumors) and toxic effects were determined. Results: The low dose ATO alone has no pronounced effects on tumor growth delay compared to untreated control. However, compared with radiation alone, the combined regimen delayed the tumor growth by 2–10 days and had no significant toxic effects such as the liver function damage. Conclusions: Combination of ATO at non-toxic dose level and radiation has synergistic effects on tumor growth inhibition in vivo and is well tolerated.